Design of fairness-driven RSMA-SDMA precoding - Yanjing SUN; Fengzhi CHENG; Jiasi ZHOU; Song LI (Tongxin xuebao)
In view of the minimum user rate and system fairness when the transmit power was limited, a user access mode selection transmission strategy by joint rate-splitting multiple access (RSMA) and space division multiple access (SDMA) was proposed.The precoding design problem of maximizing system fairness was modeled.In order to solve the discrete non-convex optimization problem formed, it was decomposed into two non-convex sub-problems, such as the user access mode selection and the inner optimal precoding design.For the precoding design, a quadratic transform of multidimensional and complex FP was used to transform the precoding design into double rotation, and the closed-form expression of the optimal solution for the outer user access mode selection was obtained.Convex optimization was used to solve the inner precoding design problem, and successively optimize the user access mode selection.An algorithm based on fractional optimization was proposed for the problem, and the optimal precoding vector was designed using the quadratic transform of multidimensional and complex FP to maximize the minimum user rate under power constraints.The simulation results prove that compared with RSMA, SDMA and other transmission strategies, the fairness-driven RSMA-SDMA precoding design improves the minimum user rate of the system and guarantees the system fairness.